Comparative evaluation of anti-diabetic activity of fresh juice and ethanolic extract of Sunderban mangrove Rhizophora mucronata Lam. leaves in animal model - Adhikari, Anjan; Ray, Moumita; Sur, Tapas K.; Biswas, Sharmistha; Das, Anup K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Mangrove flora possess compounds with potential medicinal values with unique bioactive components. Traditionally Rhizophora mucronata, a mangrove has been used extensively for the treatment of diabetes. Studies revealed that, the leaves of Rhizophora (Bhora) had promising anti-diabetic action in rat model. Methods: A comparative analysis of the anti-diabetic action of fresh juice and ethanolic extract of Rhizophora mucronata leaves was carried out in Streptozotocin induced diabetic model and the different biochemical parameters were evaluated. Results: Present research explored a comparative analysis of the anti-diabetic action of fresh juice and ethanolic extract of leaves of Rhizophora mucronata Lam. in Streptozotocin induced diabetic model. The ethanolic extract showed more potent effect in lowering the elevated blood sugar in the diabetic rats, 200mg/kg was the most effective dose for both the extracts. The ethanol extract was more beneficial having potent lipid lowering action along with anti-hyperglycemic property. Conclusions: This supports the scientific validation for using Rhizophora mucronata leaves in the treatment of diabetes as traditional folk medicine. Identification of the bioactive molecule is under process.